Análise da implantação da política de saúde da população negra no Estado de Sergipe - Correia, Miraci dos Santos (2015)
The study analyzed the participation of representatives of the State and civil society in the "State Technical Committee for the Promotion of Equity and Popular Education in Health", in the process of implementation of the "Health Policy of the Black Population of the State of São Paulo" Sergipe, "through a review of their careers .The research utilized documentary records, minutes, interviews and observations during the meetings.The time cut was from 2013 to 2014, when the Committee was created. Constructed from the perspective of totality and that social, political and economic aspects interfere in the organization, formulation and implementation of a policy. The research concludes that the municipality is a space for the exercise of democracy, the experiences of the councilors should be taken in So that, together with militancy and professional practice, they build the knowledge that allows them to participate, they are knowledgeable actors of the social cause, by participating in decision-making spaces, they increase their knowledge and feel valued there. Networks of relationships and training space embedded in a process, in a context of social movements, are essential for engagement in the Commission. The scenario points to an empty policy, making it little active, with little political force. You have to take the streets and squares, so it's not just a matter of blacks.